Nutrition, fertility, and human reproductive function - Tremellen, Kelton; Pearce, Karma (Boca Raton : CRC Press, Taylor & Francis Group, 2015)
'One in six couples around the world experience infertility and they often seek advice from their physician or dietitian before they undertake expensive and intrusive assisted reproductive treatment such as in vitro fertilization. This book provides a comprehensive review of the role of nutrition in human fertility, focusing on the impact of diet and nutritional supplements on essential reproductive processes in women such as ovulation, early embryo development, implantation, and sexual function. It also examines impact on male reproductive hormones and sperm production'--
Includes bibliographical references and index.
Keywords: Nutritional Physiological Phenomena; Reproductive Physiological Phenomena; Reproductive health